CROSS-BORDER COOPERATION OF POLISH SELF-GOVERNMENT ADMINISTRATION IN THE LIGHT OF THE RELATION BETWEEN ADMINISTRATIVE AND INTERNATIONAL LAW - Tyrawa, Dominik (Review of European and Comparative Law, 2016)
The purpose of the article is to indicate relations which appear between administrative law and international law, then, to discuss the specificity of international cooperation of local/regional authorities with particular attention paid to the essence of cross-border cooperation. Instead of a conclusion, the author decided to conduct an in-depth analysis of cross-border cooperation of local/regional authorities and refer this cooperation to the relation between administrative law and international law.